STRATEGI SEKOLAH ISLAM DALAM MENCEGAH PERILAKU BULLYING - Kartika, Nadya Putri; Astutik, Anita Puji (PAI RAFAH, 2024)
This research discusses Islamic school strategies in preventing bullying behavior in schools, due to the increasing cases of bullying both verbal and non-verbal bullying lately. This research aims to explain the strategy of Islamic schools in Pasuruan Regency, especially SMPN 2 Kraton. The research method used in this study is descriptive qualitative with data collection techniques of observation, interview, and documentation. The research subjects include an Islamic education teacher and a counseling guidance teacher, this research took place at SMPN 2 Kraton, Pasuruan Regency, East Java Province. The findings of this study provide the results of several strategies used to prevent bullying behavior, namely by conducting socialization related to bullying, the existence of personal counseling services and group guidance, being a good role model, religious habituation such as reading the Qur'an together before learning and praying dhuhur in the congregation, making anti-bullying declarations, installing CCTV in certain areas, making anti-bullying boxes and PPK (strengthening character education) programs.